Loss of Interleukin (IL)-10 Is Associated With Increased Vascular Inflammation and Sex-Differences in Metabolic Outcomes of Normal Diet-Fed Mice. (7th June 2021) - Alake, Sanmi; Ojo, Babajide; Kaur, Amritpal; Hermann, Evan; Ice, John; Chowanadisai, Winyoo; Lin, Dingbo; Smith, Brenda; Lucas, Edralin
Abstract: Objectives: The anti-inflammatory cytokine, IL-10, plays an important role in reducing the risk of many inflammatory diseases. This study investigated the time and sex effects of IL-10 gene deletion on metabolic risk factors that contribute to the development of cardiovascular disease. Methods: Six-wk-old male and female B6.129P2-Il10 tm1Cgn /J (IL-10 −/− ) and C57BL/6 (WT) mice ( n  = 12–16/group) were randomly assigned to 12- or 24-wk time points and were fed growth (AIN-93G) diet up to 3 m of age and then maintenance diet (AIN-93M) for the remainder of the study. Monthly fasting glucose was assessed as well as intraperitoneal glucose tolerance test (ipGTT), body composition, and serum metabolic parameters at each study end point. Cardiac and vascular adhesion molecules, macrophage marker F4/80, and sterol metabolism genes were assessed using qPCR. Data were analyzed using t-test and 2-way ANOVA with strain and gender as factors, and α = 0.05. Results: IL-10 deletion resulted in weight loss ( p < 0.05 ) coinciding with reduced fat mass and % fat ( P  < 0.05) in both sexes of IL-10 −/− . Loss of IL-10 had no effect on fasting glucose at any time point in either sex; however, a delayed response to glucose challenge and increased AUC with the ipGTT ( P  < 0.05) occurred in male IL-10 −/− vs WT mice. No strain effect was observed on serum lipids at 12 wks, but cholesterol and high-density lipoprotein (HDL)-C were reduced ( P  < 0.05) in IL-10 −/− vs WT mice at 24 wks. Only male IL-10 −/− mice exhibited elevated ( P  < 0.05) non-HDL cholesterol and tended ( P  = 0.072) to have elevated triglycerides vs WT mice at 24 wks. In conjunction with serum lipid changes, male IL-10 −/− mice increased ( P  < 0.05) hepatic transcription of β-hydroxy β-methylglutaryl-CoA (HMG-CoA), whereas HMGCoA transcript tended to be repressed (≥ −53.5%; P  = 0.08) in female IL-10 −/−  vs WT mice. At 12 and 24 wks, IL-10 −/− exhibited increased ( P  < 0.05) circulating c-reactive protein and aortic and cardiac gene expression of VCAM-1, ICAM-1, and iNOS . The only increase in the F4/80 macrophage marker occurred in male IL-10 −/− mice vs WT at 24 wks. Conclusions: Loss of IL-10 was associated with different metabolic responses in male and female mice and could be detrimental to cholesterol-mediated metabolic processes in female mice on a control diet. Funding Sources: Oklahoma Agriculture Experiment Station and the Jim and Lynn Williams Professorship.